Soft ideals of soft ternary semigroups. Issue 6 (June 2021) - Kar, S.; Dutta, I.
Abstract: In this paper, we introduce the notions of certain classes of soft ideals in soft ternary semigroups and study some inter-relations between different types of soft ideals in a soft ternary semigroup. We also characterize completely regular soft ternary semigroups with the help of these soft ideals of soft ternary semigroups. Abstract : Soft ternary semigroup; Soft prime ideal; Soft semiprime ideal; Soft irreducible ideal; Soft bi-ideal; Soft prime bi-ideal; Soft semiprime bi-ideal; Soft completely regular ternary semigroup